A Giuseppe Dessí. Lettere di amici e lettori Con un'appendice di lettere inedite - Nencioni, Francesca (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2009)
This book, the result of a lengthy labour of cataloguing and research, continues the indexing and recording of the unpublished epistolary material conserved in the Dessí fond, launched in 2003 by Chiara Andrei with the edition of the family correspondence (Firenze, FUP). Now, through 1,900 letters from friends and readers, Francesca Nencioni offers a different and more ample overview of the fundamental stages in the life and works of the writer, focusing above all on the years of his university training in Pisa. Of particular interest is the appendix of carefully annotated unpublished texts, which offers 19 letters from Dessí to friends and scholars, the complete two-way correspondence with Walter Binni, and the letters sent to the friend and disciple of the great historian, Delio Cantimori. Press reviews: 26/10/2009: Dessì e la voce "lontana e bianca" del 1955 12/2009: "L'immaginazione" n. 251